2019
DOI: 10.1007/s13280-019-01167-0
|View full text |Cite
|
Sign up to set email alerts
|

Governing evolution: A socioecological comparison of resistance management for insecticidal transgenic Bt crops among four countries

Abstract: Cooperative management of pest susceptibility to transgenic Bacillus thuringiensis (Bt) crops is pursued worldwide in a variety of forms and to varying degrees of success depending on context. We examine this context using a comparative socioecological analysis of resistance management in Australia, Brazil, India, and the United States. We find that a shared understanding of resistance risks among government regulators, growers, and other actors is critical for effective governance. Furthermore, monitoring of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 60 publications
0
57
0
Order By: Relevance
“…In addition, individuals from lower educational backgrounds were under-represented in the focus groups. Studies have shown that perceptions of environmental issues, such as air quality, are affected by education level, along with other socio-demographic factors, such as age and gender [ 66 ]. Further studies highlighted the need to raise awareness and interest in exposure to chemicals and environmental issues among lower socioeconomic groups [ 67 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, individuals from lower educational backgrounds were under-represented in the focus groups. Studies have shown that perceptions of environmental issues, such as air quality, are affected by education level, along with other socio-demographic factors, such as age and gender [ 66 ]. Further studies highlighted the need to raise awareness and interest in exposure to chemicals and environmental issues among lower socioeconomic groups [ 67 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Seed mixtures may benefit resistance management by ensuring farmer compliance with refuge requirements and facilitating matings between resistant individuals surviving on Bt crops and susceptible individuals from refuges for pests with low adult dispersal 7,8,10–12 . However, for any given percentage of refuge plants, evolution of resistance is expected to be faster with seed mixtures than block refuges for pests with larvae that move extensively between plants or feed on corn ears 7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…This strategy could be effective if the following assumptions are met: resistance alleles to a Bt protein are rare; a Bt protein is consistently produced by a plant at a highly toxic concentration, with resistance alleles that are functionally recessive; and cultivation of refuge areas with non-Bt plants [10]. Refuges of non-Bt crops can be a source of Bt-or insecticide-susceptible individuals that contribute to delaying resistance [11,12]. Ideally, these refuges are planted near Bt crop fields or fields where critical insecticides are used to allow Bt-resistant insects to mate with susceptible insects produced in refuges [13].…”
Section: Introductionmentioning
confidence: 99%